Determinan Pembiayaan Bagi Hasil Perbankan Syariah Di Indonesia: Model Regresi Panel - Al Arif, M Nur Rianto; Nurhikmah, Ika (AL-FALAH : Journal of Islamic Economics, 2017)
Financing is one of the performanceâs indicator in Islamic banking industry. The aim of this research is to examine the factors that influence the financing in the Indonesian Islamic banking industry. The method that used in this research is panel regression with fixed effect model. The variabels that used in this research are capital ratio, profitability ratio, default rate, liquidity ratio, efficiency ratio, deposit fund, inflation, and profit sharing yield. The result shows that the capital ratio, profitability ratio, efficiency ratio, deposit funds, and profit sharing yield had an impact on financing in the Indonesian Islamic banking industry. This result implies that the Islamic banks should maintain the internal factors to increase the financing in the Islamic banking industry.